Sistem Informasi Pemesanan Jasa Fotografi Berbasis Web pada Uncle Photo - Pradana, Muhammad Iqbal; Mariana, Novita (Jurnal Teknologi Sistem Informasi, 2024)
Uncle Photo is a bussines in the field of photography and videography which is located at Jl. Raya Banaran Rt 1 Rw 4, Sekaran, Gunung Pati, Semarang City. The products offered by this business include photo and vidio albums. Using PHP framework, Boostrap CSS framework and MySQL as the database. To build this website for the sale licenses to make it easier for licenses users to do business and communicate online. Customers who need photography and videography service can choose various packages on the Uncle Photo Website. The conclusion from Uncle Photo’s research is that web and online ordering can run well according to the input and output made by user so that customers can place orders and store owners and employees get detailed and detailed order reports. The system also provides an attraction for users, Uncle Photo alsohas a vision to provide the best service for customers and gain customer trust.